English Lexical Errors Committed by Algerian Learners The Case of Second Year University Students - Meriem MAZRI (Revue des Sciences Humaines, 2015)
This paper investigates the lexical errors committed by Algerian learners of English in their written compositions; our main aim is to analyse their lexical deviations following James’s (1998) taxonomy, and to find the reasons that lead them to err. The obtained results revealed that errors of distortion are the most frequent error type followed by collocations. The main source of errors is the learners’ serious lack of vocabulary knowledge in form and meaning.